How to Install Twines in a Hopyard - Shinsuke Agehara; Christopher DelCastillo (EDIS)
Because of the rapidly growing craft beer industry and rising hop prices, the potential of hops as an alternative crop is currently being investigated at the UF/IFAS GCREC. Proper installation of twines is critical to facilitate easier crop management and harvesting. This new article by explains how to install twines on a 18-ft hop trellis. It is part of a series that reviews the challenges of hop production in Florida. Written by Shinsuke Agehara and Christopher DelCastillo; 3 pp. https://edis.ifas.ufl.edu/hs1418